2000
DOI: 10.1017/cbo9780511612527
|View full text |Cite
|
Sign up to set email alerts
|

State Formation in Early Modern England, c.1550–1700

Abstract: This book examines the development of the English state during the long seventeenth century, emphasising the impersonal forces which shape the uses of political power, rather than the purposeful actions of individuals or groups. It is a study of state formation rather than of state building. The author's approach does not however rule out the possibility of discerning patterns in the development of the state, and a coherent account emerges which offers some alternative answers to relatively well-established qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 417 publications
(32 citation statements)
references
References 0 publications
0
30
0
2
Order By: Relevance
“…In this paper we develop a new perspective on state formation, emphasizing the idea that aspects of state weakness, particularly the lack of monopoly of violence in peripheral 1. The classic example is the disarmament of the English aristocracy by the Tudors following the Wars of the Roses (Storey 1968), which allowed for the development of the state (Elton 1953;Braddick 2000), ultimately culminating in the reforms implemented after 1688 (Brewer 1988). areas, can be an equilibrium outcome which "modernization" need not automatically change. Although we believe that the ideas proposed in this paper have relevance both in democratic or nondemocratic contexts, we develop a model formalizing these notions in the context of a democratic country.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper we develop a new perspective on state formation, emphasizing the idea that aspects of state weakness, particularly the lack of monopoly of violence in peripheral 1. The classic example is the disarmament of the English aristocracy by the Tudors following the Wars of the Roses (Storey 1968), which allowed for the development of the state (Elton 1953;Braddick 2000), ultimately culminating in the reforms implemented after 1688 (Brewer 1988). areas, can be an equilibrium outcome which "modernization" need not automatically change. Although we believe that the ideas proposed in this paper have relevance both in democratic or nondemocratic contexts, we develop a model formalizing these notions in the context of a democratic country.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that the design of public services has been of great importance for the internal cohesion of the community and for the creation of collective identities (Braddick, 2000;Epstein, 2006;He, 2015;Slack, 1999). Thus, the organisation of public services contributes to a society's perception of the significance of the public, and it is this consciousness that makes up publicness.…”
Section: The Construction Of 'Publicness'mentioning
confidence: 99%
“…As Michael Braddick has observed, 'the success of measures against nonconformity depended on the willingness of secular authorities to give teeth to national legislation: national panics did not necessarily find a resonance in all localities'. 107 In Cumberland and Westmorland the vigour with which Sir Philip Musgrave and Daniel Fleming approached the prosecution of Quakers during the period 1660-64 has been allowed to obscure the fact that here too, some officials were clearly more active than others -a phenomenon recognised by the Quakers themselves.…”
Section: IVmentioning
confidence: 99%